PENGELOLAAN KEGIATAN KOKURIKULER DALAM MENUMBUHKAN KARAKTER RELIGIUS DI MTS AMIR AL-JANNAH BAJOE - Syawaluddin Alfalah, Muh; Aditya, Farham; Luktafiani, Sri; HM, Amir (DIDAKTIKA, 2022)
This study is intended to describe the management of co-curricular activities in growing the religious character of students at MTs Amir Al-Jannah Bajoe. The specific purpose of this study is to describe the planning, implementation and evaluation of co-curricular activities in fostering religious character. This type of research is based on a qualitative approach. The location or setting of this research is MTs Amir Al-Jannah Bajoe. Sources of research data are school principals, teachers in charge of curriculum and students. Data collection techniques, observation, interviews and documents. The results of the study, Management of co-curricular activities in fostering religious character, related to planning, implementation, and evaluation. Careful planning of co-curricular activities can make it easier for each activity that has been mutually agreed upon by the principal, teachers, student coaches, in carrying out co-curricular activities. The implementation of co-curricular activities can be done by focusing more on the religious character of students because they are considered important. co-curricular evaluation is based on knowing how high the level of success of the planned activities for future decision making is.